Differential prospective relationships of social-oriented and individual-oriented achievement motivations with achievement goals and affective wellbeing: A 1-year follow-up study. (June 2023) - Tao, Vivienne Y.K.; Kam, Chester Chun Seng; Li, Yun; Wu, Anise M.S.
Abstract: This study aimed to investigate the differential prospective relationships of social-oriented achievement motivation (SOAM) and individual-oriented achievement motivation (IOAM) with student's adoption of specific achievement goals and their affective wellbeing (AWB). A total of 332 Chinese university students ( M age  = 19.139; Female = 75%) voluntarily participated in the baseline and the 1-year follow-up surveys of this study. The factor score path analysis results showed statistically significant positive paths from SOAM and IOAM at baseline to performance goals and mastery goals, respectively, at follow-up. Moreover, a statistically significant positive path was found from SOAM at baseline to negative affective experiences, at follow-up, and no association was found between IOAM and AWB, after controlling for achievement goals. The findings suggest the usefulness of raising educators' and parents' awareness regarding the double-edged sword of utilizing socially valued motives to promote performance approach goals in individuals because such values potentially lowering their psychological wellbeing. Highlights: Adds a socially-oriented view to study Chinese students' learning and adjustment. Individual-oriented achievement motivation (IOAM) predicts future mastery goals. Social-oriented achievement motivation (SOAM) predicts future performance goals. IOAM does not predict future Chinese students' affective experiences. Only SOAM predicts future negative affective experiences over achievement goals.